Factors Affecting Carpal Tunnel Syndrome in End Stage Renal Disease with Maintenance Hemodialysis: A Systematic Review (World Journal of Current Medical and Pharmaceutical Research, 2021)
Introduction: The number of patients with End Stage Renal Disease (ESRD) is increasing every year, as well as those who have to undergo hemodialysis. Most hemodialysis must be undertaken in a long time. Long term hemodialysis is known to be associated with the incidence of Carpal Tunnel Syndrome (CTS).Method: This study aimed to systematically review factors contributing in the mentioned problem. Literature research was done using three search engines, consist of Google Scholar, Pubmed and ProQuest. Journals used are limited to the last 5 years or those deemed to be relevant. The studies obtained were further read and and appraised critically.Result and Discussion: From a total of 423 journals, 4 articles were selected based on inclusion and exclusion criteria. The prevalence of CTS was found to be higher in ESRD patients undergoing maintenance hemodialysis (MHD). Age, Gender, MHD Duration, β2-Microglobulin are factors that have long been known to play a role. Several other factors such as serum prealbumin, serum albumin, Blood Lead Levels, hepatitis infection, wrist injury, predialytic urea serum and BMI have been implicated in the incidence of CTS in ESRD patients undergoing MHD in some literatures.Conclusion: The factors mentioned earlier were found to have different roles and it is interesting for further reviewed. However, unfortunately there is still very little research that discuss these matters and more research needs to be done related to the factors above.